Kortsigtede økonomiske virkninger for Nanortalik ved en kommunesammenlægning - Lars Lund (Copenhagen Business School (CBS), Department of Economics, 2006)
A new local government structure is announced for Greenland from 2009. If the reform is carried through, Nanortalik the most southerly town will come together with Qaqortoq, then the new centre, and Narsaq. A suggestion by the mayor of Nanortalik about the number of civil servants that should move to the centre is the basis for calculating the potential loss of gross income (wages and profits) in the first years of the reform. With the civil servants follow some adults and children. On top of the direct loss of income come derived losses determined by a multiplier process. The size of the multiplier is estimated to be around 1,25. This is based on assumptions about income levels, expenditure patterns, and local income parts of sales. Full implementation of the reform could mean a loss of 5 plus percent of gross income. If other probable losses (e.g. fewer elected members of the local authority) are added in, the loss could rise to more than 7 percent. Tax rates are assumed not to be lowered by the departure of civil servants to the centre. To the contrary an increase in the tax rate for Nanortalik is envisaged as this small town in these years enjoys an advantage from taxing local people and foreign skilled workers operating a nearby gold mine. It is stressed that the paper doesn't evaluate the proposal for a reform, neither for the South of Greenland nor for Greenland as a whole. It is about possible very short term local effects
hdl:10398/7521
Keywords: G10; 330